Aktualisasi Diri Komika Berkebutuhan Khusus - Ahmad Rajibullah; Fattah Hanurawan; Gamma Rahmita U. Hakim (Fakultas Psikologi Universitas Negeri Malang, 2020)
In 2011, stand-up comedy began to appear as new spectrum of Indonesian entertainment industry. All kinds of people start to pursue career as a comic, some of them are people with special needs. Stand-up comedy becomes one of the ways that people with special needs can utilize to develop a potential they might have. This research is focused on discovering the self-actualizing concept of comics with special needs and how they complete the characteristics of selfactualized people. This research is using qualitative approach with case study type of research. After going through analyzing process on the findings, this research comes to conclusion as follows. The sefactualization concept of comics with special needs is a distinctive actualization in self-acceptance, creativity, and humor with further adjustment in autonomy and cultural aspects. The subject’s process to reach the characteristic of a self-actualizing individual is consists of self-acceptance phase in wich subjects questioned their physical condition, feeling inferiority, then later accepting their self by the support of family and realistic perception about their physical condition. Self-acceptance leads subjects to develop their potential and began to reach self-actualization.